A new synonym of the biting midge, Culicoides bottimeri Wirth, with a redescription, new distribution records and seasonal activity data (Diptera: Ceratopogonidae) - Phillips, Robert A.; Grogan, William L.; Mullens, Bradley A. (Zootaxa, 2006)
We provide evidence that the North American biting midge, Culicoides multidentatus Atchley & Wirth, is a junior objective synonym of C. bottimeri Wirth (new synonym). A detailed comparison of paratypes of both species with recently collected specimens from California and Utah revealed that only one species is represented in the southwestern United States. Also provided are redescriptions, illustrations, and photographs of key characters of both sexes of C. bottimeri, as well as new distribution records from California and Utah (new state record), and seasonal activity data from Utah.